2015
DOI: 10.5535/arm.2015.39.3.425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Head Rotation and Head Tilt on Pharyngeal Pressure Events Using High Resolution Manometry

Abstract: ObjectiveTo observe changes in pharyngeal pressure during the swallowing process according to postures in normal individuals using high-resolution manometry (HRM).MethodsTen healthy volunteers drank 5 mL of water twice while sitting in a neutral posture. Thereafter, they drank the same amount of water twice in the head rotation and head tilting postures. The pressure and time during the deglutition process for each posture were measured with HRM. The data obtained for these two postures were compared with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In the hypotonic UES group, the median of HADS score were for HADS-T 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), HADS-A 7(5-10) and HADS-D 6(3-8). In the normotonic UES group: for HADS-T 13(9-19), HADS-A 8(5-11) and HADS-D 6(3.75-8).…”
Section: Results Resultsmentioning
confidence: 99%
“…In the hypotonic UES group, the median of HADS score were for HADS-T 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), HADS-A 7(5-10) and HADS-D 6(3-8). In the normotonic UES group: for HADS-T 13(9-19), HADS-A 8(5-11) and HADS-D 6(3.75-8).…”
Section: Results Resultsmentioning
confidence: 99%
“…In HRM studies, parameters related to UES opening, such as UES relaxation time 44–46 and minimum UES pressure, 44,45 have often been reported. The minimum UES pressure in healthy individuals was around 0 mmHg 43,47 and significantly increased in patients with dysphagia 43 . Massey reported that UES relaxation time is more sensitive and reliable in identifying UES dysfunction than UES pressure because UES pressure was sensitive to emotional stress, speech, and neck movements 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The channels of interest were velopharynx (VP), tongue base (TB), epiglottis, pharyngeal constrictors, and preand post-swallow upper esophageal sphincter (UES). These channels were defined manometrically in accordance with previous reports [7,[14][15][16]. Variables included maximal pressure and area integral in regions of VP and TB.…”
Section: Methodsmentioning
confidence: 99%